Insights into the subtitling of films from Arabic into Spanish - Noha Abdallah Mohamed Moussa; Miguel Angel (Universitat Jaume I. Department of English Studies, 2021)
Audiovisual translation studies (AVT) have experienced an exponential growth in the last twenty years, have consolidated proven analysis methodologies, and attracted the interest mainly of Western scholars. It is interesting to investigate whether these methodologies are also applicable to the study of subtitling of films from linguistically and culturally distant cultures such as Egyptian and Spanish. Therefore, the main objective of this work is to verify whether the translation norms proposed in the translation methods for dubbing and subtitling, traditionally based on language combinations with English, are applicable for the specific case of the Arabic-Spanish language combination, based on the analysis of the treatment of the cultural elements present in the audiovisual texts selected for this research. Among the findings, the distinctive features and colloquial character and spontaneity of the original versions are frequently lost.